2011
DOI: 10.4236/cm.2011.23016
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Traditional Phytotherapy among the Inhabitants of Lahaul Valley through Amchi System of Medicine—A Cold Desert Area of Himachal Pradesh in North Western Himalayas, India

Abstract: The paper highlights the Phyto-diversity and indigenous uses an ecosystem existing in Lahaul Valley of tribal district of Lahaul and Spiti in Himacjhal Pradesh, India. This is one of the most preferred tourist spot especially for foreigners. The cold desert area of India is known for its specific topography, sense climate and unique vegetation. The valley is rich in high value medicinal wealth and local inhabitants (Buddhist) practice the Tebetan Amchi System of Medicine. Keeping in view the continuous pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The plant is very popularly used amongst many tribes across India and in the regions falling around the Himalayan belt for treating diseases. Selinum vaginatum is popular amongst Gujjar tribe, Jaad Bhotiya Community Bhotia tribe, Lahaul valley, tribals from Parbati valley, district Chamba of Western Himalaya, Bhotia tribe of Mana village, Nanda Devi Biosphere reserve, local inhabitants of Banaun, tribal inhabitants from Garhwal, Chamoli, Uttarakhand, South India and many other regions ( Arya et al., 2018 ; Balodi et al., 2018 ; Chauhan, 2014 ; Gairola et al., 2014 ; Garbyal et al., 2005 ; Kumar et al., 2019 ; Malik et al., 2015 ; Nand and Naithani, 2018 ; Radha and Puri, 2019 ; Radha et al., 2019 ; Rana et al., 2010 , 2013 , 2019 ; Rana and Samant, 2011 ; Semwal et al., 2010 ; Sharma et al., 2004 , 2011 , 2013 ; Singh et al., 2009 ; Thakur et al., 2017 ). However, the effect of Selinum vaginatum in diabetic complications has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The plant is very popularly used amongst many tribes across India and in the regions falling around the Himalayan belt for treating diseases. Selinum vaginatum is popular amongst Gujjar tribe, Jaad Bhotiya Community Bhotia tribe, Lahaul valley, tribals from Parbati valley, district Chamba of Western Himalaya, Bhotia tribe of Mana village, Nanda Devi Biosphere reserve, local inhabitants of Banaun, tribal inhabitants from Garhwal, Chamoli, Uttarakhand, South India and many other regions ( Arya et al., 2018 ; Balodi et al., 2018 ; Chauhan, 2014 ; Gairola et al., 2014 ; Garbyal et al., 2005 ; Kumar et al., 2019 ; Malik et al., 2015 ; Nand and Naithani, 2018 ; Radha and Puri, 2019 ; Radha et al., 2019 ; Rana et al., 2010 , 2013 , 2019 ; Rana and Samant, 2011 ; Semwal et al., 2010 ; Sharma et al., 2004 , 2011 , 2013 ; Singh et al., 2009 ; Thakur et al., 2017 ). However, the effect of Selinum vaginatum in diabetic complications has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…O. hispida is used as a medicinal herb [ 30 , 31 ] exhibiting various biological properties including antibacterial activity [ 32 ]. The plant O. hispida has been reported to be used as blood purifier and for cuts, swells, wounds [ 33 ]. And it has also been reported for the treatment of abdominal ulcers, hair problems, bladder and kidney stones and rheumatism [ 34 ], pneumonia, typhoid fever and also used for dyeing hairs [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that dried root powder of CT cure severe joint pains. [10,11] It is also found effective in curing headache, stomach problems, measles, and boils. There is very scarce literature present regarding this plant, and little information is available about the biological effects of its constituents.…”
Section: Abstract a R T I C L E I N F Omentioning
confidence: 99%